Patient journey following lumbar spinal fusion surgery (LSFS): protocol for a multicentre qualitative analysis of the patient rehabilitation experience (FuJourn). Issue 1 (3rd January 2018) - Rushton, Alison; Staal, J Bart; Verra, Martin; Emms, Andrew; Reddington, Michael; Soundy, Andrew; Cole, Ashley; Willems, Paul; Benneker, Lorin; Masson, Annabel; Heneghan, Nicola R
Abstract : Introduction: There has been a 65% increase in lumbar spinal fusion surgery (LSFS) worldwide over the last 13 years, with costs of £26 million to the UK National Health Service annually. Patient dissatisfaction with outcome and persistent pain and disability incurs further costs. Three trials provide low-quality evidence for the role of physiotherapy. Our UK surveys investigating physiotherapy/surgeon practice concluded rehabilitation should be tailored to the individual patient owing to considerable clinical heterogeneity. This study will explore the perceptions of patients who undergo LSFS to inform precision rehabilitation. Methods and analysis: A qualitative study, using interpretive phenomenological analysis, will recruit a purposive sample (n=40) to ensure patterns of similarity and difference in their journeys can be explored. In-depth semistructured interviews will be undertaken following discharge from hospital and at 12 months postsurgery. Patients' preoperative and postoperative experiences, underlying attitudes and beliefs towards the surgical intervention, facilitators and barriers to recovery, adherence to advice and physiotherapy, experiences of rehabilitation and return to normal function/activity/work will be explored. A 12-month patient diary will provide real time access to patient data, capturing a weekly record of life as lived, including symptoms, medication, experiences of stages of recovery, rehabilitation adherence, healthcare professional appointments, attitudes, their feelings and experiences throughout their journey. Data will be analysed in a number of stages in accordance with interpretive phenomenological analysis, supported using NVivo software. Analysis of the first interviews and patient diaries will afford a rich density of data to build an overall understanding of the patients' lived experiences, informing the 12-month interview. Strategies (eg, reflexivity) will ensure trustworthiness. Ethics and dissemination: The study has ethical approval (IRAS 223283). Findings will ensure that patient-driven data inform precision rehabilitation by understanding the patient journey. Findings will be disseminated through peer-reviewed journals and conferences.